PENGARUH PENGETAHUAN KEWIRAUSAHAAN TERHADAP KEBERHASILAN DALAM BERWIRAUSAHA (STUDI KASUS PADA MASYARAKAT PEDAGANG PASAR V TEMBUNG KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG) - Hartanti, Trika; Hadian, Arief (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This study aims to determine whether knowledge of entrepreneurship has an effect on success in entrepreneurship in the Merchant Community of Pasar V Tembung, Percut Sei Tuan District, Deli Serdang Regency. In data collection techniques, namely using a questionnaire distributed to all respondents. Data created with the help of SPSS 15.0 for window. The data analysis technique used by the researcher is simple linear regression, with the formula Y=a+bx+e, and to determine the magnitude of the influence of entrepreneurial knowledge on entrepreneurial success, significant changes use the t-test or (parsia). The results showed that the simple linear regression test obtained the equation Y=14,297+0,360x+e, the regression coefficient of entrepreneurial knowledge was 0.360. The value of the coefficient of determination (R2) is obtained with a value of 0.162 or 16.2%, which means that entrepreneurial knowledge affects the success of a business. To find out that the hypothesis is accepted or rejected in the study, the t-test technique used is 4.048 with ttable of 1.988, thus it is accepted because tcount> ttable. Therefore, this research can be said that entrepreneurial knowledge has a significant effect on success in entrepreneurship in the Pasar V Tembung Merchants community, Percut Sei Tuan District, Deli Serdang Regency. keywords: Entrepreneurship Knowledge, Business success.